Adoption of Sustainable Rangeland Management (SRM) toolkit by the two main development agencies in Tunisia to ensure sustainable restoration of degraded agrosilvopastoral systems - CGIAR Research Program on Livestock (2021)
ICARDA, IUCN, and NARS in Tunisia have developed an SRM toolkit that addresses the root causes of rangeland degradation. The tried-and-tested toolkit has been adopted by national and international development agencies in Tunisia. Its use is highly appreciated by pastoral communities due to its flexibility to adjust grazing strategies, taking into account indigenous knowledge coupled with science-based technologies. The projected results include better management and restoration of rangelands in dry areas, where demand for accessible and productive land is increasing.